Poverty and inequality: drivers of migration - Rivera Rosales, Valentín; Alcaraz Vera, Jorge Víctor; Chávez Rivera, Rubén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Causes that generate migration, establish the differences between the sending and receiving countries of migrants, some 100 million more people fell into extreme poverty as a result of the pandemic (COVID-19), climate change may push up to 132 million people into extreme poverty by 2030, the majority of the poorest people in the world will live in situations characterized by fragility, conflict and violence, triggering large migratory flows, taking as a reference a great inequality. You cannot compare the lifestyles of the developed worlds, especially in Western countries, where waste is common, where money is the god that is venerated.